Individualized aerobic-power training in an underperforming youth elite association football player - Mujika, I.; Santisteban, J.; Angulo, P.; Padilla, S. (International Journal of Sports Physiology and Performance, 2007)
Aerobic and anaerobic power are fitness traits of major relevance to association football (soccer) performance. A player`s competitive performance could suffer when either or both of these fitness qualities decline because of ineffective training. The principle of training individualization dictates that training benefits are more likely to be optimized when training programs reflect individual athletes` needs and capacities but this principle is often neglected in team-sport settings. In this study, we report on the case of an underperforming youth elite player whose aerobic power had clearly declined over several months. A 7-week individualized training program was prescribed and implemented in an attempt to improve his performance level.